The New York Times circuits how electronic things work - Fountain, Henry (St. Martin's Press, 2001)
Presents illustrated essays from the New York Times' Circuits section explaining how a variety of high-tech gadgets and appliances work, including digital cameras, touch pads, TV remote controls, fuel cells, laser vision correction, and bar codes